2015
DOI: 10.1017/s1751731115001433
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the tissues composition of pork belly

Abstract: Bellies derived from the commercial population of pig carcasses are diverse in terms of tissue composition. Knowledge of the factors influencing it and the expected results, permits quick and easy evaluation of raw material. The study was designed to determine the factors affecting the tissues composition of pork bellies and to estimate their lean meat content. The research population (n = 140 pig carcasses) was divided into groups according to sex (gilts, barrows), half-carcass mass (<40, 40 to 43.9, 44 to 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The highest number of statistically significant P ≤ 0.05 strong and moderate correlations (Huff-Lonergan et al, 2002) was noted for location D3. On the other hand, the lowest number of such correlations (Duziński et al, 2015) was observed for four locations: D1, M4, A2, and A1. In general terms, the weakest correlation was demonstrated in the abdominal plane, and the strongest in the dorsal plane.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…The highest number of statistically significant P ≤ 0.05 strong and moderate correlations (Huff-Lonergan et al, 2002) was noted for location D3. On the other hand, the lowest number of such correlations (Duziński et al, 2015) was observed for four locations: D1, M4, A2, and A1. In general terms, the weakest correlation was demonstrated in the abdominal plane, and the strongest in the dorsal plane.…”
Section: Resultsmentioning
confidence: 88%
“…Full evaluation of physical and sensory qualitative feature characteristics and their dependencies can be used to obtain precise processing and consumer information about this element. Unfortunately, bellies from mass populations are currently characterized by differentiation of tissue composition (Duziński et al 2015). Additionally, the fat and meat distribution in the belly is heterogeneous and highly dependent on the location and also the selection of the population (Fredeen 1980;Brewer et al 1995;Correa et al 2006;Trusell et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations